The morphology and optical properties of organic molecules and heterostructures. - Alkhamisi, Manal (2020)
By growing optically active small organic molecules on insulating substrates, the interplay between their optical properties and structural control imposed by molecular self-assembly and the formation of molecular heterostructures can be explored. Controlling the arrangement of molecules within nano-structures is of great interest as a means to develop materials with novel optical and electronic properties. The first part of this body of work deals with the case of the self-assembly of free-base phthalocyanine (H2Pc) monolayers on hBN. Needle-like islands were found to arrange on the surface with orientations reflecting the symmetry of the underlying hBN lattice, which has three axes of rotational symmetry. The unit cell of this organic monolayer was extracted from high resolution AFM images and found to be aPc= bPc= 2.2 ± 0.03 nm and aPc= bPc = 2.18 ± 0.05 nm for room temperature and higher substrate temperature growth respectively. These lattice vectors were also found to be subtended by an angle θ= 86°. The vibrationless optical transition (0-0) of H2Pc monolayers adsorbed on hBN (1.879 eV) was measured using steady state photoluminecence, and was found to be red shifted by ∆E= 0.13 eV. The ZnPc molecule was also investigated, and was found to form islands with a height (0.6 ± 0.1 nm), consistent with molecules adsorbed in a non-planar geometry. Fluorescence spectroscopy was carried out on the ZnPc layers on hBN, with a peak observed at 1.82 eV. The growth of NTCDI on hBN, resulted in the formation of anisotropic monolayer islands with height of 0.3 ± 0.1 nm. As the substrate temperature was increased, the size of islands was found to increase, and the island morphology changes to a lily- pad shape for further increased in temperature growth. Upon a description of the growth of NTCDI films, the formation of heterostructures produced by sequential deposition of PTCDI/NTCDI, and NTCDI/PTCDI on hBN/SiO2 was then discussed. Heterostructures of thick hBN flakes and monolayers of PTCDI were formed using mechanical flake transfer. The change in properties of the encapsulated material was explored with photoluminescence (PL). This simple case of PTCDI encapsulated by hBN approach offers numerous opportunities to fabricate technologically relevant devices, such systems offer many opportunities to fabricate electronic devices where structure can be imposed on the molecular and monolayer thickness length scales in the in-plane and out-of-plane directions respectively. Finally, the self-assembly of PCDA molecules on hBN and HOPG surfaces was carried out using different solvents and different concentrations. Highly ordered islands grown on these surfaces were observed using AFM. The self-assembled molecules on hBN were exposed to UV light (245 nm), and the light induced polymerisation of these was discussed. The intensity of the PL response increased as a result of increasing the exposure time.